Anti-spoofing methods in face recognition - Foteini Filippidou; Bezas, Konstantinos (AI Society & STMIK Indonesia, 2023)
Biometric data are personal data that result from specialized processing techniques and are associated with physical, biological, or behavioral characteristics of a natural person that allow for or confirm their unquestionable identification. These characteristics or identifiers are permanent and unique. This paper refers to the biometric characteristics used by systems, their mode of operation, and the categories they are distinguished in. The types of attacks that they may be subjected to are then analyzed, along with the anti-spoofing methods proposed in some studies specifically for systems that use the face as a biometric feature. Finally, numerical data is presented regarding the scientific interest that the topic of anti-spoofing methods in biometric systems has shown in the last decade.